Cultivating Ethics and Empathy through Character Building to Prevent Acts of Sexual Violence and Bullying - Susilowati, Susilowati - (Journal of Innovation and Applied Technology, 2024)
This community service aimed to develop a character-building program at SMPN 15 Kota Malang to prevent sexual violence and bullying among students by fostering ethics and empathy. The service involved several activities, including initial surveys to identify risk factors, curriculum development, training for teachers and staff, and workshops for parents. The implementation focused on cultivating students’ understanding of ethics and empathy through interactive learning and group discussions. The program evaluation indicated significant improvements: 85% of students reported increased awareness of empathy, while bullying and sexual violence cases decreased by 35%. Additionally, parental involvement in school activities increased by 50%. These results suggest that the program effectively fostered a safer, more inclusive school environment and should be expanded to other schools.